Presenting the model of tax compliance: the role of internal and psychologival factors / Seyyed Yaser Ebrahimian Jolodar, Masoud Ahmadi and Niloofar Imankhan. - Jolodar, Seyyed Yaser Ebrahimian; Ahmadi, Masoud; Imankhan, Niloofar (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2019)
Today, the concept of tax compliance has become a common phenomenon in most countries and attracted the attention of a large number of researchers in order to identify the affecting factors on it. In this regard, the purpose of this research is to exploration the main internal and psychological factors affecting on tax compliance and in return try to present the tax compliance model. The statistical population of this study included 2900 legal persons of Sari tax administration in Iran who shall be liable to Value-Added Tax (VAT). The sampling technique in this study was stratified random sampling and the sample size comprises of 550 legal persons. The findings revealed a significant and positive impact of tax fairness, taxpayers' attitude, trust in authorities and tax morale on tax compliance. Furthermore, the results of the study showed that tax compliance is largely determined by tax morale. Moreover, the results suggest that tax authorities should take more concentration on tax fairness for creating favorable attitude in taxpayers, enhancing trust in authorities and improvement of morale obligation.